La contingence des guidages en danse - Lucile Lafont; Marie-France Fanton-Bayrou (Éducation et Socialisation)
This study examines how an expert PE teacher with a background in dance helps students during tutorial interactions in the context of complex situation instruction (CSI). From the socio-cultural perspective (Bruner, 1983), we observe the contingency elements of the teacher’s guidance that contribute to the decrease or increase of the control over the students’ behaviors in complex situation of collective creation-production (CS) and targeted learning-reproduction of techniques situation (TS). The observation took place in a very heterogeneous mixed class of 27 students (11-12 years old) during a regular dance cycle. The class includes a few students from a structure of school inclusion. The interactive episodes analyzed qualitatively with regard to the students’ behaviors for each of the situations show more contingent and emancipating verbal and gestural guidance in the case of the CS in comparison with the TS.